Advancements in less-invasive aortic root, ascending aorta and arch surgery: current evidence and future directions (Swiss Medical Weekly, 2025)
Aortic surgery is one of the most challenging areas in cardiovascular medicine because of the complexity of the procedure and the potential for life-threatening complications. Historically, median sternotomy has been the gold-standard approach for thoracic aortic interventions, providing excellent exposure to the entire ascending aorta and the distal aortic arch. This approach has yielded satisfactory postoperative results over the years. However, the invasiveness of median sternotomy is associated with significant surgical trauma, increased postoperative pain and prolonged recovery. Minimally invasive aortic surgery has emerged as a potential alternative to conventional approaches with the aim of combining the benefits of minimally invasive cardiac surgery with the demands of complex aortic interventions. In this review, we aimed to critically analyse the current experiences with minimally invasive aortic surgery via partial upper sternotomy for the treatment of aortic root, ascending aorta and aortic arch pathologies. The partial upper sternotomy (PUS), as a less invasive approach in minimally invasive aortic surgery, represents a substantial advancement in the field of aortic surgery. The current literature on minimally invasive aortic surgery via PUS is predominantly based on retrospective, single-centre studies with small sample sizes, which limits the strength of the conclusions and generalisability. Ventilation time, intensive care unit (ICU) stay, length of hospital stay and bleeding complications can be reduced using this approach. Survival was not negatively affected and cosmetic results were improved by minimally invasive aortic surgery.